2021
DOI: 10.1155/2021/9087816
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Pathway of PGE2 and Its Regulatory Role in T Cell Differentiation

Abstract: Prostaglandin E2 (PGE2) is a lipid mediator derived from the fatty acid arachidonic acid. As an essential inflammatory factor, PGE2 has a critical impact on immune regulation through the prostanoid E (EP) receptor pathway. T cells, including CD4+ and CD8+ T cell subsets, play crucial roles in the adaptive immune response. Previous studies have shown that PGE2 is involved in regulating CD4+ T cell differentiation and inflammatory cytokine production via the EP receptor pathway, thereby affecting the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 58 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…As the expression of CD73 can be induced by PGE2 on macrophages [ 25 ] and PGE2 is a well-known regulator of T cell differentiation and plasticity [ 26 ], we first verified if adult SC could produce PGE2. First, analysis of mRNA expression of the inducible form of cyclooxygenase (COX-2), the major enzymes in prostaglandin production, revealed that SC express COX-2 mRNA and its level in SC could be significantly up to three-fold up-regulated by SC pre-exposure to the melanoma-conditioned medium ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…As the expression of CD73 can be induced by PGE2 on macrophages [ 25 ] and PGE2 is a well-known regulator of T cell differentiation and plasticity [ 26 ], we first verified if adult SC could produce PGE2. First, analysis of mRNA expression of the inducible form of cyclooxygenase (COX-2), the major enzymes in prostaglandin production, revealed that SC express COX-2 mRNA and its level in SC could be significantly up to three-fold up-regulated by SC pre-exposure to the melanoma-conditioned medium ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that PGE2 regulates the activation, maturation, differentiation, migration, and other activities of immune cells. 7 , 17 For example, PGE2 reduces the production of interleukin (IL)‐12 in monocytes or dendritic, which selectively prevents the differentiation of naïve CD4 + T cells into Th1 cells. 18 , 19 Chen et al showed that PGE2 suppressed the function of antigen‐specific CD8 + T cells and promoted the apoptosis of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although PGE2 has a short half‐life, it has a key role in mediating inflammation and a variety of biological processes in vivo. Previous studies have demonstrated that PGE2 regulates the activation, maturation, differentiation, migration, and other activities of immune cells 7,17 . For example, PGE2 reduces the production of interleukin (IL)‐12 in monocytes or dendritic, which selectively prevents the differentiation of naïve CD4 + T cells into Th1 cells 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 exerts its biological activity mainly through four recognized receptors (EP1-EP4) [ 22 ]. From those receptors, EP2 and EP4 have been shown to possess immunosuppressive effects, enhancing the cAMP-PKA signaling pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%